Classification Analysis of the Assessment of the Community Satisfaction Index for Public Service Mall Services Based on Education Using Decision Tree - Nelviony Parhusip; Muhammad Iqbal; Sri Wahyuni (Yayasan Sinergi Multidimensi Kreatif, 2024)
This study aims to analyze the classification of the Community Satisfaction Index (CSI) assessment of Public Service Mall (PSM) services based on the level of education using the Decision Tree algorithm. Assessment of public satisfaction with public services is very important to improve the quality of services, and educational factors can affect the perspective and assessment of the services received. The data used in this study is secondary data on Medan City SMEs collected from January to September 2023. The research process includes data collection, preprocessing, and modeling using the Decision Tree algorithm with the help of RapidMiner software. The results of the analysis showed that respondents with higher education levels, such as D3, S1/D-IV, S2, and S3, tended to give better assessments of PSM services, with most of them giving Excellent (4) and Good (3) scores. In contrast, respondents with lower education, such as high school and junior high school, gave more varied assessments, although the score of Very Good (4) was still dominant in most respondents. This study suggests that PSM managers consider educational factors in designing and improving the quality of public services to meet the diverse expectations of society. Further research can explore other factors that affect community satisfaction, such as age or user experience.